Innovation in the Processing of "Balinese Arak" based on Bananas, Specially Asah Duren Village, Pekutatan District, Jembrana Regency, to Support Ecotourism Development - Ni Luh Putu Putri Setianingsih; Gregoria S. Suhartati Djarkasi; A.A. Made Semariyani; I Wayan Sudiarta; Ni Made Ayu Suardani Singapurwa; Luh Suriati; I Gede Pasek Mangku; I Putu Candra; Sang Ayu Made Agung Prasetiawati Djelatik; Gusti Ngurah Oka Jiwantara; I Putu Ajus Raditya Putra (Asian Journal of Community Services, 2023)
The body needs a lot of nutrients from bananas, which have a lot of nutritional content. Natural bananas contain no fat, cholesterol, or sodium. Bananas can be processed into processed products such as wine or "Balinese Arak," made from bananas. The following is a nutritional description of bananas. "Balinese Arak," an alcoholic beverage made from fermented bananas, is one of the most valuable banana derivative products. Appropriate steps are needed to solve the problems faced by farmer women's groups. One effort that can be made is to encourage people to learn food processing techniques and to make "Balinese Arak" from bananas. Partners fully understand how to properly process banana-based "Arak Bali" products